ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUH KINERJA SISTEM INFORMASI AKUNTANSI DI MASA PANDEMI COVID-19 (Studi Kasus Pada Usaha Mikro Kecil Menengah di Kota Mojokerto) - Faizatur Hafidhoh; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aimed to determine the effect of user involvement, personal technical ability, training and education, and top management support on accounting information system performance. This study uses a quantitative approach. The sample used in this study uses the purposive sampling method. Analysis of data testing with Multiple Linear Regression Methods. This research shows that Personal technical ability has a significant positive effect on accounting information system performance. Training and education have a significant positive effect on the performance of accounting information systems. Top management support has a significant positive effect on accounting information system performance. Keywords: User involvement, Personal technical skills, Training and Education, Top management support